2006
DOI: 10.1021/jp063110m
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Electrochemical Micromachining of n-GaAs and p-Si by Using Confined Etchant Layer Technique

Abstract: The confined etchant layer technique has been applied to achieve effective three-dimensional (3D) micromachining on n-GaAs and p-Si. This technique operates via an indirect electrochemical process and is a maskless, low-cost technique for microfabrication of arbitrary 3D structures in a single step. Br(2) was electrogenerated at the mold surface and used as an efficient etchant for n-GaAs and p-Si; l-cystine was used as a scavenger, for both substrates. The resolution of the fabricated microstructure depended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Previous studies using a microelectrode as the mold have shown the best etching resolution is around 500 nm, when the concentration of scavenger is much larger than that of the etchant. [35] Moreover, when the concentration of HBr is increased and the generated Br 2 at 1.0 V cannot be consumed by the inadequate scavenger near the mold, this causes lateral diffusion of the etchant according to the principle of CELT. Surprisingly, when the concentration of HBr in the etching solution is increased, etched microstructures are still obtained with the same etching precision and a better uniformity is achieved.…”
Section: =2 (4)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using a microelectrode as the mold have shown the best etching resolution is around 500 nm, when the concentration of scavenger is much larger than that of the etchant. [35] Moreover, when the concentration of HBr is increased and the generated Br 2 at 1.0 V cannot be consumed by the inadequate scavenger near the mold, this causes lateral diffusion of the etchant according to the principle of CELT. Surprisingly, when the concentration of HBr in the etching solution is increased, etched microstructures are still obtained with the same etching precision and a better uniformity is achieved.…”
Section: =2 (4)mentioning
confidence: 99%
“…Previous studies have shown that the etching resolution by CELT is always better for micromachining on GaAs than on Si due to the faster reaction rate of etching on GaAs. [35] Thus, the heterogeneous reaction between the substrate and the etchant influences the etching resolution. When the influence of the heterogeneous reaction on the etching resolution or the thickness of CEL needs to be taken into account, Equation 5 can account for the concentration of species O (Br 2 ) as a function of distance x from the plate-like working electrode and separation d. Equations 6 and 7 only give the concentration distribution of the confined etchant layer, regardless of the reaction between the GaAs and the etchant.…”
Section: =2 (4)mentioning
confidence: 99%
“…[25] Parallel electrode arrays have also been used with fixed arrangements of the individual electrodes but without lateral repositioning of the array. [26,27] The necessity of leveling samples relative to the horizontal (x,y) plane of the positioning system adds another technical difficulty that is especially evident for bent and rough samples.…”
mentioning
confidence: 99%
“…In order to confine the lateral extension of etched areas, the confined etchant layer techniques was introduced and refined (Scheme 1c). [27,28,29] In the ME-substrate gap, Br 2 is also consumed by a homogeneous reaction with a scavenger, for instance L-cystine. [29] ME-sample gap:…”
Section: Me Probe : 2 Brmentioning
confidence: 99%